PENGEMBANGAN UJI VISUAL SEDERHANA DARI KUALITAS BERBAGAI KOMPOS DAN PERBANDINGANNYA DENGAN UJI LABORATORIUM DAN UJI PERCOBAAN LAPANGAN - Syafitra Ibadillah; T. Sabrina; Razali Razali (Universitas Sumatera Utara, 2014)
At the market, composts are sold varied in their quality. Some of them are originated fromforest floor and other are collected from burnt and half- decomposed municipal waste. Thereis no control for commercial compost by government, thus many of composts sell at marketare not registered. Buyers should able to detect the good and bad compost quality in thesimple ways. This present experiment was conduct to develop a new simple visual test todetect the good and bad compost quality and comparing test result with the test result oflaboratory analysis and field experiment. The composts used in this experiment were:vermicompost (made by researcher), 2 burnt municipal waste (burned by researcher) and 8commercial composts. Simple test consist of several parameters viz color, odor, react ofcompost when put into water, The compost laboratory analysis were: pH, carbon organic,total nitrogen, ratio, C/N, total microorganism number, water holding capacity, compostparticle size composition. The field experiment test was conducted in the screen house usingmustard as an indicator plant. The experiment design was randomized block with 12treatments (vermicompost as a control for good compost, 2 burnt municipal waste compostsas a control for bad compost, 8 commercial composts and without adding compost) and 3replications. The result showed that the color of burnt municipal waste composts weregrayish, while the color of vermicompost was dark brown. No Odor of burnt municipalwaste compost was founds, while the odor of vermicompost was humid odor. All of theburnt municipal waste composts were sinking into the bottom of glass when it puted intowater, and not for vermicompost. Almost all of compost solid from forest floor was floatingwhen puted into water. The laboratory analysis test showed the burnt municipal compostshad the lowest C organic, N total content, C/N, and total microorganism number, and had thehighest pH value compare to other composts. The tests showed that some of commercialcomposts quality were bad. Meanwhile, the result of field experiment test did not gave thesignificant effect on the growth and production of mustard (Brassica juncea) using good orbad compost quality compare to control (without adding compost). As conclusion, the badquality of compost especially the burnt municipal waste compost, and the forest floorcompost were able detect using simple test by putting it into water.Keywords : vermicompost, burnt municipal waste, commercial compost, simple test,laboratory test, field experiment test